Menelusuri Pengaruh Kepemimpinan Situasional dan Dinamika Kelompok terhadap Produktivitas Tim di Pondok Pesantren Darul Arifin Jambi - Suci Karlina Aziz; M. Rasyid; Jamrizal Jamrizal; Samsu Samsu (Moral : Jurnal kajian Pendidikan Islam, 2025)
The results of the research show that there is a significant influence between situational leadership and group dynamics on team productivity at the Darul Arifin Islamic Boarding School in Jambi. Situational leadership: Mentors and administrators at the Darul Arifin Islamic Boarding School in Jambi demonstrate good adaptability in providing guidance and direction to the team. Group dynamics: There is a positive relationship between effective communication, good cooperation and team productivity. Teams that are able to establish open communication and support each other show higher productivity. Team Productivity: Teams that have good situational leadership and positive group dynamics show increased productivity in carrying out tasks and achieving targets. This is reflected in the level of satisfaction of students, improving the quality of education, and the active role of students in Islamic boarding school activities.